Evaluation of the increased stiffness for the elastic coupling under the dynamic loading conditions in a ship. (October 2016) - Han, HyungSuk; Lee, KyoungHyun; Park, SungHo
Abstract: Torsional vibration is restricted during design because it can cause fatigue fractures of the shaft due to repetitive vibratory torque and should be verified by analytical calculations as well as experiments. Torsional vibration is a characteristic of propulsion systems and is strongly related to their natural frequency; differences between measured and analytically predicted torsional vibration could be caused by variation of parameters related to natural frequency such as stiffness, damping, and components' inertial masses. In this investigation, extreme torsional vibration caused by increased coupling stiffness is expected to be the main root cause of fracture. The variation of coupling stiffness is investigated in a laboratory excitation test in order to determine the root cause of increased stiffness. Torsional vibration analysis error is identified as the main cause, where calculated values are quite different from measured results. It is shown that this difference is caused by torsional stiffness differences between the cases of the analytic model and the real ship. Highlights: The fracture of the gear input shaft in a typical naval vessel is investigated by numerical analysis. The coupling stiffness is measured in a laboratory to determine the cause of increased stiffness. The coupling stiffness is increased due to the low amplitude and high frequency of the real torque.